The Impact of Sanitary and Phytosanitary Measures on Market Entry and Trade Flows - Pramila Crivelli; Jasmin Gröschl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
In an attempt to disentangle the impact of sanitary and phytosanitary (SPS) measures on trade patterns, we estimate a Heckman selection model on the HS4 disaggregated level of trade. We find that aggregated SPS measures constitute barriers to agricultural and food trade consistently to all exporters. But conditional on market entry, trade flows are positively affected by SPS measures. Additionally, we find that SPS measures related to conformity assessment hamper market entry and trade flows, while SPS measures related to product characteristics pose an entry barrier but increase bilateral trade flows conditional on meeting the standard
Keywords: C23; F14; Q17; 330; Agriculture; international trade; sanitary and phytosanitary measures; conformity assessment; Heckman selection model; Lebensmittelüberwachung; Markteintritt; Agraraußenhandel; Schätzung; Welt